Ancient teeth, phenetic affinities, and African hominins: Another look at where Homo naledi fits in. Issue 122 (September 2018) - Irish, Joel D.; Bailey, Shara E.; Guatelli-Steinberg, Debbie; Delezene, Lucas K.; Berger, Lee R.
Abstract: A new species of Homo, Homo naledi, was described in 2015 based on the hominin skeletal remains from the Dinaledi Chamber of the Rising Star cave system, South Africa. Subsequent craniodental comparative analyses, both phenetic and cladistic, served to support its taxonomic distinctiveness. Here we provide a new quantitative analysis, where up to 78 nonmetric crown and root traits of the permanent dentition were compared among samples of H. naledi (including remains from the recently discovered Lesedi Chamber) and eight other species from Africa: Australopithecus afarensis, Australopithecus africanus, Paranthropus boisei, Paranthropus robustus, Homo habilis, Homo erectus, Middle Pleistocene Homo sp., and Pleistocene and Holocene Homo sapiens . By using the mean measure of divergence distance statistic, phenetic affinities were calculated among samples to evaluate interspecific relatedness. The objective was to compare the results with those previously obtained, to assess further the taxonomic validity of the Rising Star hominin species. In accordance with earlier findings, H. naledi appears most similar dentally to the other African Homo samples. However, the former species is characterized by its retention and full expression of features relating to the main cusps, as well as the root numbers, with a near absence of accessory traits—including many that, based on various cladistic studies, are plesiomorphic in both extinct and extant African hominins. As such, the present findings provide additional support for the taxonomic validity of H. naledi as a distinct species of Homo .